Beam commissioning of the first clinical biology‐guided radiotherapy system. Issue 6 (28th April 2022) - Han, Bin; Capaldi, Dante; Kovalchuk, Nataliya; Simiele, Eric; White, John; Zaks, Daniel; Xing, Lei; Surucu, Murat
Abstract: This study reports the beam commissioning results for the first clinical RefleXion Linac. Methods : The X1 produces a 6 MV photon beam and the maximum clinical field size is 40 × 2 cm 2 at source‐to‐axis distance of 85 cm. Treatment fields are collimated by a binary multileaf collimator (MLC) system with 64 leaves with width of 0.625 cm and y‐jaw pairs to provide either a 1 or 2 cm opening. The mechanical alignment of the radiation source, the y‐jaw, and MLC were checked with film and ion chambers. The beam parameters were characterized using a diode detector in a compact water tank. In‐air lateral profiles and in‐water percentage depth dose (PDD) were measured for beam modeling of the treatment planning system (TPS). The lateral profiles, PDDs, and output factors were acquired for field sizes from 1.25 × 1 to 40 × 2 cm 2 field to verify the beam modeling. The rotational output variation and synchronicity were tested to check the gantry angle, couch motion, and gantry rotation. Results : The source misalignments were 0.049 mm in y ‐direction, 0.66% out‐of‐focus in x ‐direction. The divergence of the beam axis was 0.36 mm with a y‐jaw twist of 0.03°. Clinical off‐axis treatment fields shared a common center in y ‐direction were within 0.03 mm. The MLC misalignment and twist were 0.57 mm and 0.15°. For all measured fields ranging from the size from 1.25 × 1 to 40 × 2 cm 2, the mean difference between measured and TPS modeled PDD at 10 cm depth was −0.3%. The mean transverse profile difference in the field core was −0.3% ± 1.1%. The full‐width half maximum (FWHM) modeling was within 0.5 mm. The measured output factors agreed with TPS within 0.8%. Conclusions : This study summarizes our specific experience commissioning the first novel RefleXion linac, which may assist future users of this technology when implementing it into their own clinics.